Pollen morphology of Agropyron Gaertner in Turkey - Özler, Hülya; Cabi, Evren; Us, Ebru; Do?an, Musa; Pehlivan, Sevil (Bangladesh Journal of Plant Taxonomy, 2009)
Pollen morphology of Agropyron cristatum (L.) Gaertner. s.s. (subsp. incanum (Náb?lek) Melderis and subsp. pectinatum (M. Bieb.) Tzvelev, latter including var. pectinatum and var. imbricatum (Roemer & Schultes) G. Beck) in Turkey has been studied by using light microscope and scanning electron microscope. The above-mentioned taxa are homogenous in both aperture type and exine ornamentation. Pollen grains are monoporate (rarely diporate in the case of var. imbricatum) having scabrate grouped exine surface. The scabra density and the height of scabrae as well as other morphological parameters such as annulus and operculum diameter are peculiar features for differentiation of taxa. Two different phenograms were created with the UPGMA (Unweighted Pair Group Method with Arithmetic mean) clustering technique using quantitative measurements of the pollen grains. Keywords: Agropyron; Pollen morphology; SEM; Turkey. DOI: 10.3329/bjpt.v16i1.2743 Bangladesh J. Plant Taxon. 16(1): 21-28, 2009 (June)